Herbivore Fronts Shape Saltmarsh Plant Traits and Performance - Serina S. Wittyngham; David S. Johnson (Ecology and Evolution, 2025)
ABSTRACT Herbivore fronts can alter plant traits (chemical and/or morphological features) and performance via grazing. Yet, herbivore‐driven trait alterations are rarely considered when assessing how these fronts shape ecosystems, despite the critical role that plant performance plays in ecosystem functioning. We evaluated herbivore fronts created by the purple marsh crab, Sesarma reticulatum , as it consumes the cordgrass, Spartina alterniflora , in Virginian salt marshes. Sesarma fronts form at the head of tidal creeks and move inland, creating a denuded mudflat between the tall‐form Spartina low marsh (trailing edge) and the short‐form Spartina high marsh (leading edge). We quantified Sesarma front migration rate, tested if Sesarma herbivory altered geomorphic processes and Spartina traits at the trailing and leading edges, and examined how these trait changes persisted through the final 8 weeks of the growing season. Sesarma front migration in our region is two times slower than fronts in the Southeast United States, and Spartina retreat rate at the leading edge is greater than the revegetation rate at the trailing edge. Sesarma fronts lowered elevation and decreased sediment shear strength at the trailing edge while having no impact on soil organic matter and bulk density at either edge. At the leading edge, Sesarma grazing reduced Spartina growth traits and defensive ability, and trait changes persisted through the remaining growing season. At the trailing edge, however, Sesarma grazing promoted belowground biomass production and had limited to no effect on growth or defensive traits. We show that herbivore fronts negatively impact saltmarsh plant traits at their leading edge, potentially contributing to front propagation. In contrast, plants at the trailing edge were more resistant to herbivore grazing and may enhance resilience through elevated belowground biomass production. Future work should consider herbivore‐driven plant trait alterations in the context of herbivore fronts to better predict ecosystem response and recovery.